LOWERING URIC ACID EFFICACY TEST OF THE COMBINED EXTRACT OF UNCARIA GAMBIR (HUNTER) ROXB. AND CAESALPINIA SAPPAN L. IN VIVO AND IN VITRO - Ningsih, Sri; Fahrudin, Fahri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Hyperuricemia (high uric acid levels) prevalence increased year by year. This study was aimed to elaborate the in vitro xanthine oxidase (XO) inhibitory activity and in vivo lowering hyperuricemic effect of Uncaria gambir (Hunter) Roxb) (gambir), Caesalpinia sappan L. (secang) and the combined extract of secang and gambir (formulae extract [FE]). Methods: Gambir and secang extracts were prepared by maceration with ethanol and FE was the proportioned combination of these two extracts. XO inhibitory activity was determined by measuring the formation of uric acid in the xanthine/XO system in vitro using allopurinol as a positive control at 100 ug/mL. Antioxidant activity was by 1,1-diphenyl-2-picrylhydrazyl radical reducing methods. The in vivo experiments were conducted in the oxonate-induced hyperuricemia rat model, in which FE was gavaged p.o. at the arrange dose of 75, 150, and 300 mg/kg bw for 2 weeks. Polyphenol content was measured using Folinâ€“Ciocalteu reagent spectrophotometrically. Results: The XO inhibitory activity of FE was 80% of allopurinol, while secang and gambir were 98% and 50%, respectively. The strength was appropriate to the total polyphenol content, in which it decreased in the order of secang (99%) > FE (86%) > gambir (46%). Furthermore, FE at all tested doses was able to decrease uric acid levels. FE also demonstrated antioxidant activity with a value of 74% relative to Vitamin C at 4 ug/mL. Conclusion: These studies could be concluded that FE exhibited the ability to decrease uric acid level so that it was potential to be developed further as a uric acid-lowering agent.